DEVELOPMENT OF ACADEMIC MOBILITY IN THE COUNTRIES OF THE BLACK SEA REGION IN THE CONTEXT OF GLOBALIZATION-DRIVEN EDUCATIONAL PROCESS - Бобрицька, В. І. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2016)
The article analyzes the information sources highlighting the specifics of academic mobility in the countries of the Black Sea region in the context of globalization-driven educational processes; there have been revealed the objective and subjective connections and relationships which are common to the higher education systems of the countries to have been studied and determine the commitment to sustainable development and enhancement of their intellectual, social, scientific and educational potential, as well as general academic mutual enrichment; there has been provided the overview of the peculiarities of academic mobility in the countries of the Black Sea region in the settings of progress of globalization processes